Dielectric anisotropy changes in MBBA liquid crystal doped with barium titanate by a new method - Maryam Beigmohammadi; Mahsa Khadem Sadigh; Jaafar Poursamad (Scientific Reports, 2024)
Abstract In response to the burgeoning interest in enhancing the properties of liquid crystal composites, this research systematically explores the intricate interplay between MBBA nematic liquid crystals and ferroelectric barium titanate nanoparticles. The focus is modulating dielectric properties under temperature, frequency, and an applied electric field. Nuanced insights into temperature-dependent behavior, parallel and perpendicular component alterations, and a nonlinear correlation between nanoparticle concentration and dielectric constant are revealed. The study delves into dielectric anisotropy, indicating a reduction with increasing temperature. Structural analyses validate size reduction and crystal phase maintenance of barium titanate nanoparticles (NPs), emphasizing their impact on dielectric characteristics. Frequency-dependent investigations underscore a consistent decline in permittivity with rising frequency across nanoparticle concentrations. Application of an electric field in filling process of liquid crystal cells reveals irregular changes in dielectric constant, holding promise for tailored applications in display technologies. These comprehensive findings offer valuable insights into manipulating dielectric anisotropy properties of MBBA liquid crystal by a simple method for potential advancements in optoelectronic devices and display technologies.